DAYA SAING KOMPARATIF DAN KOMPETITIF INDUSTRI KECIL GULA KELAPA - Romdon, M. Mustopa (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2004)
Development of small-scale coconut sugar industry take into account as national sector in economic region development planning has to comparative and competitive advantages.eEspecially, expectation to gill contribution enough to prosperity improvement. Using The Policy Analysis Matrix (PAM) approaches, thl study was aimed to measure the comparative advantage and the impact government's policies in development on coconut sugar in Banyumas. Its expected to contribution to development of smail-scalE industry specially coconut-sugar industry at Banyumas regency. The results showed that small-scale coconu: industries had having positive profits both private and social and had comparative and compettitiv advantages. While impact of government policy to the small-scale industry rise in toim of price of input and output. Impact on input and output price respectively indicated that producer (tappers) didn't take input subsidy and experienced disincentive in coconut sugar production. It could be concluded that the government policy didnot fully supported development of small-scale coconut sugar industry, its marked by lowest privat value-added than social value-added which could be taken by actors (tappers). For supporting the development of the industry are needed reorientation and integrated mechanism of institution mainlyempowering and marketing institution at least